Ancient and New Interpretations of Anatolian Rock-cut “Thrones” - Kisbali, Tamás Péter (Actual Problems of Theory and History of Art, 2021)
The article focuses on three rock-cut “thrones” in Anatolia: a stepped altar in “Midas City” (Phrygia), the monument of Hartapu on Kızıldağ, and the so-called “Throne of Pelops” on Mount Sipylos (Lydia). These monuments are united by similarities in their structure and location in special even “spectacular” environments. Their context in the landscape is analyzed, mainly through the visual senses: what could be observed from the monuments’ vantage point, or, on the other hand, while directing one’s gaze at the monument. Such analysis (if taking into account the discrepancies between ancient and modern landscapes, and ancient and modern experience of the observer) allows us to highlight the main accents towards which these “thrones” were oriented. In a situation where we lack other sources, these observations can enrich our understanding of the original idea of these rock-cut monuments.